STUDI PENYUSUTAN PEMBUATAN GIGI PALSU DENGAN 3D PRINTING FDM PENDEKATAN METODE TAGUCHI - Zamheri, Ahmad; Arifin, Fatahul; Syahputra, Angga Panjy (AUSTENIT, 2020)
Fused Deposition Modeling (FDM) is a 3D Printing technique used to print products using filaments as material. The printed product has ideal geometric characteristics if it has meticulous size and perfect shape. The main objective of this research is to find out the shrinkage of the material is the filament human denture product using prameter is different. In the process of testing this test using the tool testers Digimatic Vernier Caliper Mitutoyo Absolute, which uses accuracy 0,02 mm. The Taguchi method are used to analyzed the data result. Manufacture process which is used Layer Height 0,15 mm, Print Speed 20 mm/s, dan Print Temperature 220 â°C.Keywords: FDM 3D Printing, Shrinkage, TaguchiÂ